(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
Verse 100 of the comedy Acharnians by Aristophanes, the first entry of the character named Pseudartabas, has traditionally been a problem verse for both the editors of the comedy’s text and its translators. This article aims to propose an analysis of how the Aristophanic line has been rendered into English by various translators. It presents the way in which almost all published translations of the Acharnians into English (thirty-two) render the famous verse and comments on it with the hope of gaining some insight into how the translators understood the one line of Aristophanes’ comedy. As a by-product of the above endeavor, the author hopes to share with the reader the sheer pleasure of seeing how much translation potential, variety, and play there can be in a short line of ancient poetry.